Anti-coagulant Activity of Flavonoids in Medicinal Plants from Philippine Flora: A Narrative Review - Sahagun, Mark Vincent B.; Jr., Romulo R. Macadangdang; Abogadie, Clarice C.; Asi, Reah Mae C.; Boncodin, Adriel H.; Julian, Clare F.; Pedersen, Kristoffer DP. (Asian Journal of Biological and Life Sciences)
Anti-coagulants are essential in preventing the formation of clots which otherwise can lead to strokes and heart attacks if not given to people with a high risk of getting clots. Several medicinal plants that can be found in the Philippines have anti-coagulant properties and this can be attributed to the bioactive substance, flavonoids. A critical analysis of the journals, coming from Google Scholar, ScienceDirect, and PubMed, that was related to the study was conducted. We found 10 different medicinal plants from the Philippines that contain flavonoids and have an anticoagulant mechanism. Almost all the plants showed inhibition of thrombin and factor X. It was also reported that different flavonoids such as flavonols, quercetin, rutin, kaempferol, etc. are responsible for these mechanisms. The results show that medicinal plants from the Philippines particularly those containing flavonoids have the capacity to prevent coagulation and can be a potential source of treatment.
Keywords: Anti-coagulant; aPTT; Clot inhibitor; Flavonoids; Philippine medicinal plants; Prothrombin time